The muon content of extensive air showers measured by the underground muon detector of the Pierre Auger Observatory - Scornavacche, Marina (Comisión Nacional de Energía Atómica; Argentina. Gerencia de Área Académica. Gerencia Instituto de Tecnología "Jorge Sabato", 2025)
Fil: Scornavacche, Marina. Comisión Nacional de Energía Atómica; Argentina. Instituto de Tecnología "Jorge Sabato"